2016
DOI: 10.5705/ss.2014.034
|View full text |Cite
|
Sign up to set email alerts
|

Posterior propriety in Bayesian extreme value analyses using reference priors

Abstract: The Generalized Pareto (GP) and Generalized extreme value (GEV) distributions play an important role in extreme value analyses, as models for threshold excesses and block maxima respectively.For each of these distributions we consider Bayesian inference using "reference" prior distributions (in the general sense of priors constructed using formal rules) for the model parameters, specifically a Jeffreys prior, the maximal data information (MDI) prior and independent uniform priors on separate model parameters.W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 36 publications
1
27
1
Order By: Relevance
“…A priori all GP hyperparameters are independent. For the shape parameter ξ of the GEV distribution, either a diffuse prior or a weakly informative normal prior is possible (Northrop and Attalides, ). We will discuss the posterior consistency of our model under these priors in next section.…”
Section: Gp‐gev Binary Regression Modelmentioning
confidence: 99%
“…A priori all GP hyperparameters are independent. For the shape parameter ξ of the GEV distribution, either a diffuse prior or a weakly informative normal prior is possible (Northrop and Attalides, ). We will discuss the posterior consistency of our model under these priors in next section.…”
Section: Gp‐gev Binary Regression Modelmentioning
confidence: 99%
“…As stated in Section 2.2, suppose that the excess distribution F u of cluster maxima is a GPD with scale σ > 0 and shape ξ ∈ R. Further assume an improper prior for these parameters given, for all σ > 0 and ξ ∈ R, by f .σ,ξ/ .σ, ξ/ ∝ 1=σ. Note that this prior yields a proper posterior as long as the sample size is greater than 2 (Northrop and Attalides, 2016), which is the case here. Bayesian estimates and associated 95% credible intervals for the parameters are then given bŷ σ = 8:6086 ∈ .7:1258, 10:2472/, ξ = 0:0630 ∈ .−0:0464, 0:2056/:…”
Section: Bayesian Fitting Of the Distribution Of Cluster Maximamentioning
confidence: 92%
“…Further assume an improper prior for these parameters given, for all σ >0 and ξR, by f ( σ , ξ ) ( σ , ξ )∝1/ σ . Note that this prior yields a proper posterior as long as the sample size is greater than 2 (Northrop and Attalides, ), which is the case here. Bayesian estimates and associated 95% credible intervals for the parameters are then given byσfalse^=8.6086false(7.1258,10.2472false),ξfalse^=0.0630false(0.0464,0.2056false).…”
Section: Application To the Burlington Precipitation Datamentioning
confidence: 99%
“…Castellanos and Cabras () showed that the Jeffreys prior yields a proper posterior for nu1 and Northrop and Attalides () showed that under the flat prior a sufficient condition for posterior propriety is nu3. Northrop and Attalides () also showed that, for any sample size, if, and only if, ξ is bounded below a priori , the MDI prior, and the generalized MDI prior, yields a proper posterior. The way in which MDI priors are constructed (Zellner (), section ) means that the functional form of prior (11) is invariant to the particular lower bound that is chosen.…”
Section: Single‐threshold Selectionmentioning
confidence: 99%